VALUASI MANFAAT EKOLOGIS RUANG TERBUKA HIJAU (RTH) DI KOTA BOGOR DENGAN APLIKASI CITYGREEN 5.4 - Indung Sitti Fatimah; Naik Sinukaban; Aris Munandar; Kholil Kholil (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2013)
Greenery open space is a fundamental part of urban development and management in sustaining the quality of urban environment and the welfare of urban dwellers. A high rate of population growth and limited land owned causing the growth of physical development in the city is done by converting such green open space, agricultural land, forest and other open space for urban development purposes. This study is intended to analyze total value of greenery open space ecological benefits of Bogor City, and provide possible recommendations in order to increase the capacity of its urban ecosystem. This analytical framework is applied to Bogor City considering its peculiarities of greenery open space existence and architectures. The research was conducted by spatial approach through CITYGreen 5.4 software to determine the ecological benefits of greenery open space, based on the trees canopy cover and non trees canopy cover to predict the economic value. CityGreen is a software tool developed by American Forest that helps people understand the value of trees to the local environment. The result showed that CITYGreen 5.4 software can be used to conduct complex analysis of ecosystem services and create easy to understand reports.The software calculate dollar benefits for the services provided by the trees and other greenery open space in absorbed such harmfull pollutants, carbon storage and sequestration, and reducing storm water volumes as natural flood control. The capacity of ecological benefit can still be improved to provide greater benefits in various ways. This software will be very beneficial for city planners in evaluate site plan, and model development scenario that capture the benefits of trees.Keywords:greenery open space, CITYGreen 5.4, ecological benefit